ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERNAL TERHADAP SIKLUS PERSEDIAAN BARANG JADI PADA PT. GOLDEN AGIN NUSA - Mulyadi, Dodi; Setiawan, Ade Budi; Susandra, Farizka (Jurnal Akuntansi Kompetif, 2025)
Finished goods inventory is an important component in the operational management of manufacturing companies because it is directly related to smooth production, fulfilling consumer demand, and accurate financial reports. Therefore, effective internal control is very necessary to ensure inventory management runs well, avoid misuse, and minimize the risk of recording errors. In implementing an internal control system, there needs to be a basis that can be used as a reference, one of which is COSO (Committee of Sponsoring Organizations). COSO has 5 (five) internal control components, namely control environment, control activities, risk assessment, information and communication and supervision. This research aims to determine the application of the internal control system to the finished goods inventory cycle at PT. Golden Agin Nusa and knowing the suitability of implementing an internal control system for finished goods inventory at PT. Golden Agin Nusa with COSO theory. The data analysis method in this research uses a qualitative descriptive analysis method, namely by reviewing and examining, then presenting and explaining the data obtained to obtain a clear and complete description regarding the internal control treatment carried out by PT. Golden Agin Nusa. The research results show that the internal control system for the finished goods inventory cycle at PT. Golden Agin Nusa as a whole is quite suitable for implementation in accordance with internal control theory based on COSO, although there are a few shortcomings in the organizational system, where there is no separation of the functions of receiving and storing finished goods inventory which is carried out by one section only, and the delivery of information related to inventory is not yet effective.